THE CONTRIBUTION OF ISLAMIC SCIENTIST IN CIVILIZATION (The Scientific Framework In Unity of Sciences Paradigm) - Mirza Mahbub Wijaya (TAWASUT, 2022)
Abstract:This paper discusses the contribution of Muslim scientists in developing civilization. This is analyzed using the lens of the unity of science paradigm. A scientist must have critical analysis, research, and make various efforts for the development of Islamic science in globalization. Through this method, the chosen strategy is to develop scientific integration that can be taken for the development of knowledge that has been unable to dialogue with religion. Paying attention to inter-scientific relations without sacrificing autonomy between each scientific discipline and paying attention to the religious dimension of the Indonesian nation. This paper is expected to contribute to developing theoretical frameworks and practical strategies in the development of science in Indonesia.Keywords: Paradigm, Islamic Scholar, Islam and Civilization